2004
DOI: 10.1113/jphysiol.2003.051722
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recombinant human growth hormone and resistance training on IGF‐I mRNA expression in the muscles of elderly men

Abstract: The expression of two isoforms of insulin-like growth factor-I (IGF-I): mechano growth factor (MGF) and IGF-IEa were studied in muscle in response to growth hormone (GH) administration with and without resistance training in healthy elderly men. A third isoform, IGF-IEb was also investigated in response to resistance training only. The subjects (age 74 ± 1 years, mean ± S.E.M) were assigned to either resistance training with placebo, resistance training combined with GH administration or GH administration alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 59 publications
9
134
2
7
Order By: Relevance
“…It has been suggested that GH and cortisol are involved in the regulation of the mRNA expression of IGF-I and myostatin (Rennie et al 2004). This is in line with the findings of increased IGF-IEa and mechano growth factor expression after GH treatment in older subjects (Hameed et al 2004) and myostatin has been shown to be up regulated in response to elevated serum glucocorticoids (Lang et al 2001;Ma et al 2003). However, reviews of the metabolic effects of GH on human skeletal muscle concludes that the balance of evidence suggests there are no major anabolic effects of exogenous recombinant human GH in stimulating muscle protein accretion, muscle size, muscle strength, or muscle fiber characteristics in normal, healthy adult men or women, including the elderly (Rennie 2003;Liu et al 2007;.…”
Section: Discussionsupporting
confidence: 79%
“…It has been suggested that GH and cortisol are involved in the regulation of the mRNA expression of IGF-I and myostatin (Rennie et al 2004). This is in line with the findings of increased IGF-IEa and mechano growth factor expression after GH treatment in older subjects (Hameed et al 2004) and myostatin has been shown to be up regulated in response to elevated serum glucocorticoids (Lang et al 2001;Ma et al 2003). However, reviews of the metabolic effects of GH on human skeletal muscle concludes that the balance of evidence suggests there are no major anabolic effects of exogenous recombinant human GH in stimulating muscle protein accretion, muscle size, muscle strength, or muscle fiber characteristics in normal, healthy adult men or women, including the elderly (Rennie 2003;Liu et al 2007;.…”
Section: Discussionsupporting
confidence: 79%
“…In studies combining GH and exercise on muscle strength, a trend towards an increase in fat free mass and myosin heavy chain (MHC) isoforms has been demonstrated (Taaffe et al 1996, Lange et al 2002. Recent work focussing on the molecular adaptations to a 12-week training regime in older men found that GH and exercise together increased the IGF-I isoform MGF gene expression more than each individually (Hameed et al 2004). The mechanisms of GH action and intracellular signalling are not fully understood.…”
Section: Growth Hormonementioning
confidence: 99%
“…However, the difference in free IGF-I concentrations within the tissues is novel. IGF-I is expressed in muscle and tendons (1,11,19,51) and has been shown to stimulate tendon collagen synthesis in rabbit fibroblasts (1). The specific roles of the individual IGFBPs are still discussed (13,14).…”
Section: Effects On Igf-i and Igfbpsmentioning
confidence: 99%